Relationship of Parental Acceptance and Rejection with Psychological Wellness in Young Adults - Sadaf Khan , Sehar Hassan , Gul Husain , Iram Gul (Journal of Rawalpindi Medical College, 2011)
Background:This study was aimed at examining relationship of parental acceptance and rejection with self-concept, life satisfaction, self-esteem and self-efficacy in young adults. Methods: In this cross sectional study, 152 individuals, with equal representation of male and female, were included. The mean age of the participants was 25 years with minimum 12 years of education with equal representation of students and professionals. A set of standard instruments comprising of Parental Acceptance Rejection Questionnaire (PARQ), Six Factor Self-Concept Scale, General Self-efficacy scale (GSES) and Satisfaction with Life Scale (SWLS) were administered. Results: Findings of study showed high rates of parental acceptance from both fathers (60%) and (65%) from mothers. Rejection from mother was more strongly associated with poor self-concept (r=-.321; p=.000), low self-efficacy(r=-.267; p=.001) and less satisfaction with life (r=-.197; p=.01). Linear regression analysis supports that parental acceptance and rejection can predict self-concept, self-esteem, general self-efficacy and satisfaction with life among individuals. Conclusion: Parental acceptance or rejection has significant role in relation to psychological wellness and functioning in young adults.